LOCAL CULTURE BASED EXPERIMENTAL METHOD IN SCIENCE AND SOCIAL STUDIES LEARNING FOR ELEMENTARY SCHOOL STUDENTS - Dimas Qondias; Karolina Bhoki; Maria Euphrasia Ule (International Journal of Instructions and Language Studies, 2025)
This study aims to analyze the need for a local culture-based experimental method in the teaching of natural and social sciences for fourth-grade students at Hedhazitia Public Elementary School. The goal is to ensure that the approach used not only enriches students' understanding of the subject matter but also fosters appreciation for their own cultural heritage. The research method employed is descriptive qualitative. Data collection techniques in this study include observation, interviews, and documentation. Data were analyzed using a descriptive qualitative approach. Sources of data consisted of observations, interviews, and documentation involving the school principal and teachers. The results indicate a significant need and strong potential to develop a local culture-based experimental method in the teaching of natural and social sciences. Although its implementation has not yet been systematic, teachers have shown openness and a positive attitude toward this approach. Collaborative efforts among various stakeholders are needed to realize science and social studies education that is not only scientific but also rooted in local cultural values. In this way, primary education can produce students who are not only academically capable but also possess identity, character, and a sense of care for their culture and surrounding environment.